2019
DOI: 10.5812/pedinfect.92033
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Different Diagnostic Tools for Detection of Cryptosporidium in Children with Diarrhea

Abstract: Background: Cryptosporidiosis is a worldwide zoonotic parasitic disease found in children and HIV-positive individuals, and is mainly accompanied with diarrhea. Objectives: This study attempted to compare the sensitivity and specificity of acid-fast (AF) staining, polymerase chain reaction (PCR), and enzyme-linked immunosorbent assay (ELISA) methods to determine Cryptosporidium and its predominant species in diarrheal stool samples of children. Methods: In total, 221 diarrheal stool samples were collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(17 reference statements)
1
3
0
Order By: Relevance
“…Regarding age distribution of infection, the present study showed that Cryptosporidium infection was more frequent among children aged 1-5 years. These results were in agreement with Al-Jawabreh et al [44] and Mahmoudi et al [43], who reported that the highest frequency of cryptosporidiosis was in children under five years. This may be because children in this age group eat without washing their hands, lack knowledge about hygiene and immaturity of gut mucosa [45].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Regarding age distribution of infection, the present study showed that Cryptosporidium infection was more frequent among children aged 1-5 years. These results were in agreement with Al-Jawabreh et al [44] and Mahmoudi et al [43], who reported that the highest frequency of cryptosporidiosis was in children under five years. This may be because children in this age group eat without washing their hands, lack knowledge about hygiene and immaturity of gut mucosa [45].…”
Section: Discussionsupporting
confidence: 93%
“…In the present work, Cryptosporidium infection was more common among children with history of animal contact as they were (66.7%) of the total positive cases with statistically significant difference (p = 0.01). In the same manner, Hossain et al [39] and Mahmoudi et al [43] revealed a positive correlation between Cryptosporidium infection and animal contact. The infected livestock animals (cattle and sheep) have the liability to excrete a large number of Cryptosporidium oocysts, contaminate the environment, and infect individuals who live in close proximity to these animals, particularly in rural areas [47].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The fecal smear preparation, Ziehl-Neelsen staining, and microscopic observation are routinely used to diagnose cryptosporidiosis; however, these methods have been proved to be ineffectual due to low sensitivity and specificity [ 3 ] . Therefore, molecular tests have been employed for final confirmation of the diagnosis [ 4 ] , though it needs expertise and specialized equipment [ 4 , 5 ] .…”
Section: Introductionmentioning
confidence: 99%